A Parameter Optimization Approach for Optimal Control of RSSI Problem in cdma2000 1x Ev-Do Network - Ning Tian (Dianxin kexue)
In recent years, as the rapid-growth of the 3rd generation terminals, applications and services, the network load increase especially when small-flow online applications are much more popular. The RSSI problem became one of the critical bottlenecks to enhance the using experience. With the deep analysis of RSSI mechanism of cdma2000 1x Ev-Do network, the different effects on network reverse noise and user's experience of different combinations of parameters were discussed, a new parameter template was created based on the optimal control of AT transmit power. The template has applied in Jiangsu province and significantly improved the network capacity and user's experience without increasing the cost.